2023
DOI: 10.1101/2023.02.07.527499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GSK-3 inhibitor elraglusib enhances tumor-infiltrating immune cell activation in tumor biopsies and synergizes with anti-PD-L1 in a murine model of colorectal cancer

Abstract: Inhibition of GSK-3 using small-molecule elraglusib has shown promising preclinical antitumor activity. Using in vitro systems, we found that elraglusib promotes immune cell-mediated tumor cell killing, enhances tumor cell pyroptosis, decreases tumor cell NF-kappaB-regulated survival protein expression, and increases immune cell effector molecule secretion. Using in vivo systems, we observed synergy between elraglusib and anti-PD-L1 in an immunocompetent murine model of colorectal cancer. Murine responders had… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although the complexity of PD-1 regulation patterns for T cells makes it difficult for PD-1 expression status alone to discriminate between exhausted and activated T cells within the tumor microenvironment (43), our present findings demonstrated that clinical-stage GSK-3b inhibitor, 9-ING-41, which has been reported to activate and transcriptionally attenuate expression of various immune checkpoint molecules of T cells in either preclinical or clinical environment (35,44,45), in combination with oAd armed with immune-stimulatory and ECM-degrading therapeutic genes could effectively diminish PD-1 + cell infiltration into the periphery of the bladder tumor and synergistically enhanced the infiltration and recruitment of CD8 + PD-1 − T cells in both tumor and spleen (Figures 7B, C). These findings suggested that the potential risk of T-cell exhaustion via activation of PD-1/PD-L1 signaling axis could be effectively mitigated by the rational combination of HY-oAd and 9-ING-41.…”
Section: Discussionmentioning
confidence: 68%
“…Although the complexity of PD-1 regulation patterns for T cells makes it difficult for PD-1 expression status alone to discriminate between exhausted and activated T cells within the tumor microenvironment (43), our present findings demonstrated that clinical-stage GSK-3b inhibitor, 9-ING-41, which has been reported to activate and transcriptionally attenuate expression of various immune checkpoint molecules of T cells in either preclinical or clinical environment (35,44,45), in combination with oAd armed with immune-stimulatory and ECM-degrading therapeutic genes could effectively diminish PD-1 + cell infiltration into the periphery of the bladder tumor and synergistically enhanced the infiltration and recruitment of CD8 + PD-1 − T cells in both tumor and spleen (Figures 7B, C). These findings suggested that the potential risk of T-cell exhaustion via activation of PD-1/PD-L1 signaling axis could be effectively mitigated by the rational combination of HY-oAd and 9-ING-41.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, we observed a downregulation of PD-L1 expression in PanCK+ segments at the post-treatment biopsy as compared to the pre-treatment biopsies. This was unexpected as we, and others, have shown that GSK-3 inhibition upregulates tumor cell PD-L1 expression [ 8 , 55 ]. The observed decrease in PanCK+ PD-L1 expression may be a result of the late timepoint of the post-treatment biopsies, as the average time-on-study at the post-treatment timepoint was 270 days.…”
Section: Discussionmentioning
confidence: 97%
“…Elraglusib was developed as a targeted GSK3β inhibitor, and its anti-cancer effects have been variously attributed to GSK3 inhibition within cancer cells, resulting in abnormal regulation of NFkB, impaired DNA-damage responses or myc downregulation, and to immunomodulatory effects within NK and T-cells (7,13,24,25). We, and others, have reported that the drug inhibits both the α and β paralogs of GSK3, along with several other kinases in cellfree assays (10,17).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro CD3/CD28 co-stimulation model we utilised to stimulate T lymphocytes is designed to mimic T-cell responses to antigenpresenting cells in vivo, suggesting that elraglusib may have immunosuppressive effects in patients (37). However, it is important to note that elraglusib was recently shown to enhance immune cell activation, and synergise with anti-PD-L1 therapy in a mouse model of colorectal cancer (24). Whether these effects are due to direct effects on the immune system or enhanced immune engagement due to cytotoxic effects on colorectal cancer cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%